Environmental and social life cycle sustainability assessment of different packaging waste collection systems - ÇİFTÇİOĞLU, GÖKÇEN ALEV; YILAN, GÜLŞAH (ELSEVIER, 2019)
Considering the social, cultural, economic and environmental structure, source-separated collection of recyclable packaging wastes has been a huge issue for cosmopolite cities like Istanbul. To provide an effective recycling system; all source separation, collection and recycling activities should be analyzed environmentally and socially. In the scope of this study, existing and alternative municipal packaging waste management systems are analyzed and compared in terms of environmental and social impacts. The research is mainly based on a long term site observation, data collection and existing system analysis. Environmental performances of alternative scenarios are calculated based on the existing system data, whereas more site observations and interviews with stakeholders are conducted for the determination of social impacts. In the analysis of both environmental and social impacts of the scenarios, life cycle assessment used as a methodological approach. Results of the study show that informal collection systems are environmentally more effective than the formal collection systems. Even the resource consumption is high in these systems; they are still environmentally beneficial because of the high material collection rate. On the other hand, social impact assessment results indicate that informal collection system has serious social disadvantages compared to the formal systems. And finally, it is found that environmental and social weaknesses of the system could be minimized with integrated system applications.
Keywords: Packaging waste; Formal collection; Informal collection; Sustainability; Social life cycle assessment; Environmental life cycle assessment; SOLID-WASTE; MANAGEMENT OPTIONS; RECYCLING SYSTEMS; ENERGY RECOVERY; LCA; METHODOLOGY; CHALLENGES; IMPACTS